THE EFFECTIVNESS OF ENGLISH SONGS IN IMPROVING STUDENT’S LISTENING COMPREHENSION - Inka Permatasari Girsang; Noldy Pelenkahu; Nihta V. F. Liando (Program Studi Pendidikan Bahasa Inggris, 2023)
SMP Kristen Tomohon did this study with the aim of examining the efficacy of using English music media in enhancing seventh-grade students' listening abilities. In order to facilitate the process of giving material to students for learning efficiency, teachers use learning media, which can take the shape of physical or non-physical delivery vehicles. English songs serve as a teaching tool that encourages kids to learn to listen and to want to learn more about the subject. This study uses group quantitative research both before and after the experiment as part of a pre-experimental design. 25 students from seven different grades made up the study's subjects. Multiple-choice questions were used to collect data, and students answered them according to the researcher's instructions. According to the study's findings, the post-test mean score was greater than the pre-test. It can be concluded from this that it has a very significant impact on studentsâ€™ classroom learning outcomes, with an average increase of 42.5 points. Â